Image of Provincial Intellectuals in the 1930s Lithuanian Prose - Mačiulis, Dangiras (Lietuvos istorijos studijos, 2025)
The article investigates the image of Lithuanian provincial intellectuals in the Lithuanian prose of the 1930s. On the basis of the Lithuanian fiction of the time, answers to the following questions are pursued: What kind of people are attributed to the category of ‘intellectuals’? Which type of job most emphatically represents provincial intellectuals? What are the features and personal qualities of an intellectual? What/which social function is prescribed to intellectuals? In the prose depicting provincial intellectuals, the most prominent image is that of the teacher; it is denoted by several outstanding aspects. An emphasis is made on the teacher’s duty to perform various public/social duties which are perceived as commitment to get involved in the process of society modernization through educational activity while proactively participating in the public and cultural life of the local community. On the grounds of these attitudes and due to the authority attributed to the teacher, teachers find themselves in the foreground of public attention as well as under close supervision of their subordinates, thus becoming a prisoner of their expectations. Any failure to conform to the elevated expectations triggers conflict-laden outcomes. Prose texts frequently depict the older and younger generations of intellectuals being violently at odds with each other due to the ambitions of the younger generation to bring social and cultural changes to life. The public (i.e., the readers of prose on provincial intellectuals) and the literary criticism accepted this imagery of the intellectuals registered and visualized in prose works as a realistic reflection of Lithuanian provincial intellectuals, their daily life along with the issues they were encountering.
Keywords: Lithuanian intellectuals; Lithuanian provincial regions; image of the teacher; Lithuania in 1918–1940